The evolution of the location of economic activity in Chile in the long run: A paradox of extreme concentration in absence of agglomeration economies - Marc Badia-Miró (Estudios de Economía, 2015)
Chile is characterized as being a country with an extreme concentration of the economic activity around Santiago. In spite of this, and in contrast to what is found in many industrialized countries, income levels per inhabitant in the capital are below the country average and far from the levels in the wealthiest regions. This was a result of the weakness of agglomeration economies. At the same time, the mining cycles have had an enormous impact in the evolution of the location of economic activity, driving a high dispersion at the end of the 19th century with the nitrates (very concentrated in the space) and the later convergence with the cooper cycle (highly dispersed). In that context, this article describes the evolution of the location of economic activity in the long run, showing the tensions among Heckscher-Ohlin and New Economic Geography forces. I also offer a deeper analysis of the main drivers of this spatial distribution, focusing in the economic structure of the regions, the productivity levels of each specific economic sector and the evolution of market potential.
Keywords: R11; N96; 330; Regional economics; Agglomeration economies; New Economic Geography; Heckscher-Ohlin; Regional convergence